Managing delayed-onset post-traumatic stress disorder triggered by the Syrian war, COVID-19, and an earthquake: A case report on therapy for a sexual abuse survivor using continuous exposure and digital communication - Hussam Gharib; Mohamed Bassam Hayek; Ahmad Shathel Omar Dakkak; Rana Khaled; Salam Alchabani; Aya Rajoub; Mohamad Sami Mawardi; Reem Hasan Obaydo (SSM - Mental Health)
A clinically significant number of patients suffer from delayed-onset post-traumatic stress disorder (delayed-onset PTSD), where symptoms appear at least six months after the traumatic event. This case report describes the combined use of pharmacotherapy with cognitive‒behavioral therapy (CBT) and Narrative Exposure Therapy (NET) to treat symptoms of delayed-onset PTSD in a young Syrian girl who experienced recurring flashbacks of repeated sexual abuse that began several years prior. The death of her brother, the COVID-19 pandemic, and a subsequent earthquake in Aleppo-Syria at 2023 triggered memories of prolonged physical abuse, that were not contextually related. The patient coped with these distressing memories and unwanted thoughts through behavioral avoidance. She received treatment through psychiatric clinic sessions, and WhatsApp communication (due to confidentiality concerns), combining pharmacological therapy with psychological support. The treatment included cognitive restructuring, narrative exposure, and identifying triggers, leading to the reprocessing of trauma-related memories. Her PTSD symptoms reached a non-observable stage of PTSD, even when she was confronted with thoughts or contextual situations.